Effect of Focused Shock Wave Therapy on Pain and Elbow Heterotopic Ossification Following Burns. - Maged Magdy Abdel Mohsen, Maged Mohammed Mohammed Ismail, Amal Mohamed Abd El Baky (South Eastern European Journal of Public Health, 2025)
Background: Burns are devastating injuries, often resulting in significant morbidity, impairment of emotional well-being, and experienced quality of life. Objective: to evaluate the effect of focused shock wave therapy on pain and elbow heterotopic ossification following burns. Methods: Forty patients with elbow heterotopic ossification following burns participated in this study, they were selected from Kasr El-Aini (Cairo University hospitals and OM El-¬Masrieen hospitals (Ministry of Health). The patients were randomly assigned into two equal groups, 20 patients for each group. Group A (study Group) included twenty patients with elbow pain and heterotopic ossification following burns and they received both Focused Extracorporeal shockwave therapy plus the routine medical care (Etidronate, 300mg, twice a day, for 7 weeks). while group B (control Group) received only the routine medical care. Treatment consisted of 7 brief, non-invasive sessions given over 7 weeks, Each EWST treatment consisted of 3500 pulses at 4 Hz with an energy flux density in the range of 0.03 to 0.36 mJ/mm2. Evaluation for all patients was done before and after the treatment using Visual analogue scale (VAS) and Computed Tomography Scan (CTS) according to the Della Valle classification system. Results: there was highly significant reduction in VAS but in spite of the occurrence of improvement in some cases of the second records of CTS in grades in the ESWT group, there was non-significant difference from the statistical point of view, between both groups. Conclusion: The application of the focused shock wave therapy on pain and elbow heterotopic ossification following burns had only a minimal effect on some of the patient